PENGGUNAAN MODUL PENGAJARAN TUTORIAL DALAM MENINGKATKAN PEMAHAMAN MATERI SPLDV SISWA KELAS VIII SMP PADA PEMBELAJARAN MATEMATIKA DARING - Lia Devi Meitasari; Masruroh Handayani; Aflich Yusnita Fitrianna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is a classroom action research. The problem formulated in this research is whether the use of SPLDV material tutorial teaching modules can help improve the understanding of junior high school students in one school in the city of Cimahi? The purpose of this study was to examine the understanding ability of grade VIII junior high school students using tutorial teaching modules during online learning. The target indicator in this study is the result of each cycle test which shows an understanding of the concept of the SPLDV material. This research procedure consists of: (1) planning, (2) implementing the action, (3) observation and evaluation, and (4) reflection. The results of this study indicate that the understanding of the concept of the SPLDV material for class VIII junior high school students at one junior high school in the city of Cimahi has increased from the test results tested with an average value that continues to increase each cycle, namely in cycle 1 74.7 to 78.5 in the cycle. 2 and becomes 93.6 in cycle 3.